2021
DOI: 10.1002/ajp.23226
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and biogeographic history of the Saguinus mystax group (Primates, Callithrichidae)

Abstract: The Saguinus mystax group traditionally includes three species, S. mystax, S. labiatus, and S. imperator. The additional inclusion of S. inustus is argued on molecular grounds, which have an important impact on our comprehension of the phenotypical evolution and biogeography of the group. Here, we investigate the evolutionary events leading to the diversification of the S. mystax group, integrating phylogenetic, temporal, and geographic information with the current knowledge of the Amazonian paleogeographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Although there are many phylogenetic hypotheses for tamarins (Jacobs et al, 1998;Cropp et al, 1999;Tagliaro et al, 2005;Matauschek et al, 2011;Cunha et al, 2011;Buckner et al, 2015;Athaydes et al, 2021;Brcko et al, 2022), the most of last taxonomic decisions, that is, the delimitation of species was not based on those phylogenies and has used the distinguishability criteria to define the taxa. Currently, tamarins comprise 22 species and 20 subspecies (Rylands et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many phylogenetic hypotheses for tamarins (Jacobs et al, 1998;Cropp et al, 1999;Tagliaro et al, 2005;Matauschek et al, 2011;Cunha et al, 2011;Buckner et al, 2015;Athaydes et al, 2021;Brcko et al, 2022), the most of last taxonomic decisions, that is, the delimitation of species was not based on those phylogenies and has used the distinguishability criteria to define the taxa. Currently, tamarins comprise 22 species and 20 subspecies (Rylands et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Only Araripe et al (2008) enclosed both species in their study, and two significant lineages were found, suggesting the existence of two species. Furthermore, the most recent phylogenetics studies could not clarify the taxonomy of these species (Athaydes et al, 2021; Brcko et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent phylogenetics studies could not clarify the taxonomy of these species as only T . subgrisescens were analysed (Athaydes et al, 2021; Brcko et al, 2022). Only Araripe et al (2008) enclosed both species in their study, and two significant lineages were found, suggesting the existence of two species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations